DEMODECOSIS WITH DERMATITIS DUE TO FUNGAL INFECTION MALASSEZIA SP. IN SHIH TZU DOG: A CASE REPORT - Ernawati, Ni Made; Soma, I Gede; Suartha, I Nyoman (Buletin Veteriner Udayana, 2023)
A 10-year-old male Shih Tzu dog named Renbow is experiencing skin problems with signs of itching. Clinical examination showed alopecia, erythema, thickening of the skin and oily skin. On the face to the left side of the neck, the dog was injured due to scratching with a high enough intensity with swelling under the skin filled with fluid. On examination of deep skin scraping on the skin found the mite Demodex sp. amounted to 3-8 per one field of view and skin cytology examination showed the fungus Malassezia sp. with the spores. Hematological examination showed that the animal had normochromic normocytic anemia. The case dog was diagnosed with demodicosis with dermatitis due to fungal infection of Malassezia sp . The therapy given is by cleaning the injured skin using Chlorhexidine and smeared with Gentamicin and Ketoconazole (in the form of an ointment), administering the antiparasitic NexGard SPECTRA ® , Clindamycin, Cetirizine, Furosemide and fish oil . Dogs are bathed 2 times a week using a shampoo containing sulfur. Evaluation after 10 days the dog's condition has improved with reduced scratching intensity, swelling due to fluid on the neck and face has disappeared, the erythema has begun to decrease and the initially oily skin has begun to disappear. Examinations deep skin scrapping after 10 days also showed the absence of Demodex sp mites. and reduced findings of Malassezia sp . The treatment given is continued in the next two months to be re-evaluated. Dogs show improvement in condition after being given therapy and intensive care is needed for dogs to prevent re-infection.